Early Outcomes With HeartWare HVAD as Bridge to Transplant in Children: A Single Institution Experience. Issue 1 (19th November 2015) - Ferro, Giuseppe; Murthy, Raghav; Williams, Derek; Sebastian, Vinod A.; Forbess, Joseph M.; Guleserian, Kristine J.
Abstract: The HeartWare HVAD has been used as a bridge to cardiac transplantation in the pediatric population. We describe outcomes following HeartWare HVAD implantation at a single center. A retrospective chart review was performed of all HeartWare HVAD implants performed at our institution between May 2013 and March 2015. Eight children between the ages of 9 and 17 years underwent HVAD implantation as a bridge to transplant ( N  = 7 cardiomyopathy, N  = 1 complex single ventricle). There was one operative death in the complex single ventricle patient. Seven patients (87%) were successfully bridged to transplant. Median time of support was 24.5 days (range, 6–91 days). All transplanted patients are alive and well at a median follow‐up of 448 days. Our results demonstrated that mechanical support with HeartWare HVAD is feasible in patients of varying sizes (from older children to adolescents).